2016
DOI: 10.1186/s13071-016-1857-y
|View full text |Cite
|
Sign up to set email alerts
|

Trichinella spiralis paramyosin activates mouse bone marrow-derived dendritic cells and induces regulatory T cells

Abstract: BackgroundDendritic cells (DCs) are antigen-presenting cells that regulate T cell responses for many infectious diseases. The tissue-dwelling nematode Trichinella spiralis expresses paramyosin (TsPmy) not only as a structural protein but also as an immunomodulator to alleviate complement attack by binding to some host complement components. Whether TsPmy is involved in other immunomodulatory pathway and how TsPmy interacts with host DCs is still unknown.MethodsMouse bone marrow-derived DCs were incubated with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 51 publications
0
18
0
Order By: Relevance
“…Due to HLA-restriction, the allogeneic coculture system applied in our study includes the response of a limited naïve T cell population that are able to respond to allogeneic MHC complexed with self-peptides ( 71 ). This model system may better reflect the potential response to ES L1-treated DCs in vivo , compared to models with a polyclonal stimulation of T cells, especially since recent findings suggested that T. spiralis -secreted components are structurally related to some human cell components ( 39 ), so only a limited repertoire of naïve T cells may be able to respond. Moreover, these DCs impaired inflammatory Th1 and Th17 cell responses manifested as both reduced production of IFN-γ and IL-17 cytokines and the percentage of Th1 and Th17 cells, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to HLA-restriction, the allogeneic coculture system applied in our study includes the response of a limited naïve T cell population that are able to respond to allogeneic MHC complexed with self-peptides ( 71 ). This model system may better reflect the potential response to ES L1-treated DCs in vivo , compared to models with a polyclonal stimulation of T cells, especially since recent findings suggested that T. spiralis -secreted components are structurally related to some human cell components ( 39 ), so only a limited repertoire of naïve T cells may be able to respond. Moreover, these DCs impaired inflammatory Th1 and Th17 cell responses manifested as both reduced production of IFN-γ and IL-17 cytokines and the percentage of Th1 and Th17 cells, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Through the action of these products, mediated mainly by DCs, the parasite suppresses the host immune response against itself in order to survive, but it also mitigates the unwanted immune responses like those to autoantigens and allergens ( 37 ). Several studies, including our own ( 38 ), preformed in mouse model system, showed that ES L1 antigens of T. spiralis muscle larvae, or its components ( 39 ) possess the ability to induce the semi-matured DCs, which are able to induce the expansion of regulatory T cells (Tregs) in vitro . Our work using the rat model system also demonstrated that upon treatment with ES L1 antigens, DCs acquire semi-mature status and an increased capacity to induce Th2 and regulatory immune response both in vitro and in vivo ( 40 ).…”
Section: Introductionmentioning
confidence: 99%
“…Trichinella spiralis infection can protect itself from the host by inducing immune cell of host to produce large amounts of polyclonal nonspecific IgE. By saturating the IgE binding sites on the mast cell and basophils, it inhibits the binding of allergen-specific IgE and ameliorates allergic responses (Gurish et al, 2004;Erb, 2007). Cytokines produced by B cells modulate the differentiation of CD4 + T cells towards either Th1 or Th2 cells (Harris et al, 2000).…”
Section: Contribution Of Immunology To Clearing Host Inflammation In mentioning
confidence: 99%
“…Molecules released by T. spiralis Trichinella spiralis can survive for long periods in the host, and this is mediated by the parasite's ability to modulate the host immune response through the secretion of immunomodulatory molecules (Yang et al, 2013;Liu et al, 2014;Sun et al, 2015;Tang et al, 2015;Cvetkovic et al, 2016;Guo et al, 2016) (table 2). ES products released by the different life stages of T. spiralis are involved in acute inflammatory responses and modulate molecular cross-talk between the parasite and host (Sun et al, 2011;Kang et al, 2019).…”
Section: Application Of T Spiralis or Its Products In Therapy Of Tummentioning
confidence: 99%
“…Mice immunized with Ts -Pmy DNA vaccine induced a strong IL-10 response ( Wang et al, 2016 ). Immunization of r Ts -Pmy protein also induced CD4 + CD25 - Foxp3 + T cell population associated with high levels of IL-10 and TGF-β, possibly through stimulating dendritic cells ( Guo et al, 2016 ). Ts -Pmy also directly binds to human complement components C8/C9 ( Zhang et al, 2011 ) and C1q ( Sun et al, 2015 ) to inhibit the activation of human complement.…”
Section: Discussionmentioning
confidence: 99%